CIL:40266, Sus scrofa domestica, kidney epithelial cell. In Cell Image Library ... - Ferenz, Nick; Wadsworth, Patricia (UC San Diego Library Digital Collections, 2021)
Time lapse movie of a porcine kidney LLCPK1 cell stably expressing photoactivable GFP-tubulin. Fluorescence was activated at metaphase in a vertical strip between the metaphase plate and spindle pole. The activated strip moves poleward, demonstrating a marked microtubule flux during mitotic metaphase. See Fig 1A in: NP Ferenz and P Wadsworth 2007. Prophase microtubule arrays undergo flux-like behavior in mammalian cells. Mol Biol Cell 18:3993-4002 ... : Cells were imaged using a Nikon Eclipse TE300 microscope with 100x phase NA 1.4 objective lens and spinning disk confocal head (Perkin Elmer) and images captured with a Hamamatsu Orca ER cooled CCD camera every 2 sec. Photoactivation was achieved with a 5-sec exposure to 413-nm light from an X-Cite 120 lamp. See also: NP Ferenz and P Wadsworth 2007. Prophase microtubule arrays undergo flux-like behavior in mammalian cells. Mol Biol Cell 18:3993-4002 ...